IMPLEMENTASI KEBIJAKAN PENANGGULANGAN KEMISKINAN DI KOTA PAYAKUMBUH - Fittria Nazmi; Asep Ajidin (Halu Oleo University, 2024)
The purpose of this study was to analyze the process and results of poverty alleviation policy implementation in Payakumbuh City, West Sumatra. Qualitative methods were used to identify the driving factors of poverty alleviation policy implementation from the perspective of policymakers and the poor in Payakumbuh City. Data collection was conducted through semi-structured interviews. Data analysis was conducted using triangulation techniques, namely data reduction, data presentation and drawing conclusions. The results of the study found that the process of implementing poverty alleviation policies was carried out by the Regional Poverty Alleviation Coordination Team (TKPKD). The poor in Payakumbuh City received various assistance, but the implementation of poverty alleviation policies often failed due to inadequate funds, weak supervision, and invalid data. They wanted transparency of aid recipients as well as training and business capital. This study emphasizes the importance of communication and the role of bureaucratic structure in the success of the policy.